Fumigant Toxicity of Essential Oil and their Combination against Rhyzopertha dominica and Tribolium castaneum at Different Days Interval in Stored Wheat - Kumar, Ranjeet; Tiwari, S N (Journal of Postharvest Technology, 2024)
The experiment was conducted to find out fumigant toxicity of essential oils and  their combination against Rhyzopertha dominica (Coleoptera: Bostrichidae) and  Tribolium castaneum (Coleoptera: Tenebrionidae) at different days interval in  stored wheat. In this study four essential oils e.g. Murraya koenigii, Curcuma  longa, Calistimone. citrinus and Citrus reticulata and their suitable combinations  were evaluated at different days interval in stored wheat. 100 percent mortality was  achieved after twenty four hour of treatment. The essential oils of Murraya  koenigii, Citrus reticulate, Calistimone citrinus and Citrus reticulata either alone at 0.2 percent or their two component combination at 0.1 percent each or three  component combination at 0.07 percent each or four component combination at  0.05 percent each as compare to untreated control against Rhyzopertha dominica.  The Tribolium castaneum showed 100 percent mortality by M. koenigii, C.  reticulata, C. citrinus oil at 0.2 percent, M. koenigii + C. reticulata, M. koenigii +  C. citrinus oil at 0.1 percent each and M. koenigii + C. reticulata + C. citrinus oil  at 0.07 percent each and M. koenigii + C. reticulate + C. longa + C. citrinus oil at  0.05 percent each within 24 hours. The combination containing C. reticulata + C.  citrinus oil at 0.1 percent each and M. koenigii + C. reticulata + C. longa oil at 0.07  percent each caused 93.3 and 86.7 percent mortality, respectively after one days  which increased to 100 percent after two days. So, these essential oils may be utilized for the quick fumigation of stored wheat for eco friendly and sustainable  management of other stored grain insect pests.
Keywords: environment; medicinal; Anacardiaceae; sustainable; respectively; Anacardiaceae,